Archivists as amanuenses (scribes) of Indigenous knowledge*. Issue 2 (March 2019) - Laurent, Nicola
Abstract : This article uses the Return, Reconcile, Renew: understanding the history, effects and opportunities of repatriation and building an evidence base for the future project as a case study to explore the collaborative relationship between the eScholarship Research Centre and the community partners, representative organizations of the Ngarrindjeri, the Torres Strait and the Kimberley Indigenous communities. Drawing on interviews with Return, Reconcile, Renew project archivists, it explores archival issues – across the four themes of collaboration, space, time and place, neutrality and access – relating to Indigenous cultural heritage and working with Indigenous communities to make materials and knowledge accessible in culturally appropriate ways. Within the context of community rights to cultural knowledge, this paper will discuss the ongoing obligations of organizations working with Indigenous communities and records.